2016
DOI: 10.1111/apa.13609
|View full text |Cite
|
Sign up to set email alerts
|

Developmental study identifies the ages at which the processes involved in the perception of verticality and in postural stability occur

Abstract: Our findings suggest that the maturation of cortical and central processes involved in both the perception of verticality and in postural stability took place during childhood. However, maturation occurred later for vertical perception, which could imply delayed maturation of sensory integration processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
3
2
0
Order By: Relevance
“…Regarding age, our study finds no differences in the results between 7 and 10 years of age, which is in line with the results obtained by Tringali et al in 2017, who found no differences in SVV between 4 and 9 years of age [24].…”
Section: Discussionsupporting
confidence: 93%
“…Regarding age, our study finds no differences in the results between 7 and 10 years of age, which is in line with the results obtained by Tringali et al in 2017, who found no differences in SVV between 4 and 9 years of age [24].…”
Section: Discussionsupporting
confidence: 93%
“…Regarding age, our study nds no differences in the results between 7 and 10 years of age, which is in line with the results obtained by Tringali in 2017, who found no differences in SVV between 4 and 9 years of age [24]. Tringali evidences changes from the 10-11 age range, but the mean age of the 12 children scanned in that range is 11.2 ±0.2, suggesting that the sample is relatively older than our older children.…”
Section: Discussionsupporting
confidence: 93%
“…For children with neurotypical development, we did not observe any effect of the modulation of the somatosensory input, suggesting that compensatory mechanisms involved in SVV response were efficient. In one of our previous studies, we also observed that SVV response was independent from foot sensory inputs, whatever the tilt directions in healthy children (37). Similar results were obtained when exploring the effect of foam on postural control in children with neurotypical development (4).…”
Section: Discussionsupporting
confidence: 66%